2015
DOI: 10.2147/dddt.s85357
|View full text |Cite
|
Sign up to set email alerts
|

Navigating into the binding pockets of the HER family protein kinases: discovery of novel EGFR inhibitor as antitumor agent

Abstract: The epidermal growth factor receptor (EGFR) family has been validated as a successful antitumor drug target for decades. Known EGFR inhibitors were exposed to distinct drug resistance against the various EGFR mutants within non-small-cell lung cancer (NSCLC), particularly the T790M mutation. Although so far a number of studies have been reported on the development of third-generation EGFR inhibitors for overcoming the resistance issue, the design procedure largely depends on the intuition of medicinal chemists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…This comparison was performed using a hierarchical clustering based on the root mean square deviation (RMSD) of α-carbons belonging to positions of this main pocket. Even though there are several works considering pockets related to the kinase active site, quantitative structural-derived comparisons are presented here for the first time [ 49 ]. Interestingly, our findings indicate that 53 main pocket-belonging positions hold structural conformer-specific information when compared with non-pocket positions.…”
Section: Introductionmentioning
confidence: 99%
“…This comparison was performed using a hierarchical clustering based on the root mean square deviation (RMSD) of α-carbons belonging to positions of this main pocket. Even though there are several works considering pockets related to the kinase active site, quantitative structural-derived comparisons are presented here for the first time [ 49 ]. Interestingly, our findings indicate that 53 main pocket-belonging positions hold structural conformer-specific information when compared with non-pocket positions.…”
Section: Introductionmentioning
confidence: 99%
“…This highlights the need to further optimize the solubilizing group balancing its hydrophilicity and the overall polarity of the compoundin order to attain optimum cellular activities. While compounds 20 and 21 showed comparable cytotoxic activities, compound 21 was selected for optimization through the second screening cycle since its aniline headgroup (3-chloro-4-(3-(trifluoromethyl)phenoxy)aniline) was previously identified through a fragment-based drug design approach as being effective against EGFR-T790M [47]. Figures S2, S3) 3.3.…”
Section: Reduction Of the Nitro Group (R 2 )mentioning
confidence: 99%
“…The detailed structural analysis of the available crystal structures of the EGFR family, followed by a fragment-based design and an extensive docking study identified the hydrophobic group 3-chloro-4-(3-(trifluoromethyl)phenoxy)aniline as a good fit for the activity against T790M EGFR and also against HER2. [34] Compound (3) is a 6-salicyl-4-anilinoquinazoline derivative that was developed as a dual EGFR/HER2 inhibitor with IC 50 values of 0.12 M and 0.096 M, respectively. It showed 100-fold selectivity in a panel of 9 closely similar kinases.…”
Section: Quinazoline-based Inhibitorsmentioning
confidence: 99%
“…Like Dacomitinib (32), it inhibits the T790M EGFR due to its ability to covalently modify the enzyme (Figure 25) [79]. The outstanding performance of Afatinib (34) led it to be the first irreversible EGFR inhibitor approved by the FDA in 2013 for the treatment of metastatic NSCLC with activating EGFR mutations [83].…”
Section: Figure 22mentioning
confidence: 99%
See 1 more Smart Citation